Comparative effectiveness of different dual task mode interventions on cognitive function in older adults with mild cognitive impairment or dementia: a systematic review and network meta-analysis. - Hao, Yuqing; Zhao, Yajie; Luo, Huanhuan; Xie, Lanying; Hu, Huixiu; Sun, Chao (Aging Clinical & Experimental Research, 2025)
Objectives: To evaluate and compare the effects of different dual task interventions on cognitive function in older adults with cognitive impairment or dementia. Methods: We searched eight databases, including PubMed, Cochrane Library, and EMBASE, to obtain studies exclusively comprising randomized controlled trials on dual task interventions in individuals aged 60 and older with mild cognitive impairment or dementia, up to July 28, 2024. Study quality was evaluated using the Cochrane Risk of Bias Tool. Analyses included pairwise meta-analyses via Review Manager 5.4 and network meta-analyses via Stata 14.0. Results: A total of 32 RCTs involving 2370 participants were included. Dual cognitive task training had the most significant impact on global cognition (SUCRA = 79.2%, mean rank = 1.6) and motor-cognitive dual task training was the only dual task intervention with a notable improvement in executive function (SMD = 1.53, 95% CI 0.06–3.01). For physical function, dual motor task training was most effective, improving gait performance (SMD = 0.34), muscle strength (SMD = 0.28), and balance (SMD = 0.90). Motor-cognitive dual task training demonstrated the greatest effectiveness in enhancing activities of daily living (SMD = 1.50) and quality of life (SMD = 1.20), while reducing depressive symptoms (SMD = − 0.96). Conclusions: Dual cognitive task training is the most effective dual task intervention for enhancing global cognition. Motor-cognitive dual task training is the only dual task mode that significantly improves executive cognition.